Cardiovascular magnetic resonance imaging patterns of acute COVID-19 mRNA vaccine-associated myocarditis in young male patients: A first single-center experience - Evertz, Ruben; Schulz, Alexander; Lange, Torben; Backhaus, Sören J.; Vollmann, Dirk; Kowallick, Johannes T.; von Haehling, Stephan; Hasenfuß, Gerd; Schuster, Andreas (Frontiers in Cardiovascular Medicine, 2022)
Background: The risk of myocarditis after mRNA vaccination against COVID-19 has emerged recently. Current evidence suggests that young male patients are predominantly affected. In the majority of the cases only mild symptoms were observed. However, little is known about cardiac magnetic resonance (CMR) imaging patterns in mRNA-related myocarditis and their differences compared to classical viral myocarditis in the acute phase of inflammation. Methods and results: 10 mRNA vaccination associated myocarditis patients were retrospectively enrolled in this study and compared to 10 patients suffering from viral myocarditis, who were matched for age, sex, comorbidities and laboratory markers. All patients (n = 20) were hospitalized and underwent a standardized clinical examination as well as an echocardiography and a CMR. Both, clinical and imaging findings and in particular functional and volumetric CMR assessments as well as detailed tissue characterization using late gadolinium enhancement and T1 + T2 weighted sequences were compared between both groups. Median age of the overall cohort was 26 years (group 1: 25.5; group 2: 27.5; p=0.57). All patients described chest pain as the leading reason for their initial presentation. CMR volumetric and functional parameters did not differ significantly between both groups. In all cases the lateral left ventricular wall showed late gadolinium enhancement without significant differences in terms of the localisation or in-depth tissue characterization (LGE enlargement: group 1: 5.4%; group 2: 6.5%; p=0.14; T2 global/maximum value: group 1: 38.9/52 ms; group 2: 37.8/54.5 ms; p=0.79 and p=0.80). Conclusion: This study yields first evidence that COVID-19 mRNA vaccine associated myocarditis does not show specific CMR patterns during the very acute stage in the most affected patient group of young male patients. The observed imaging markers were closely related with regular viral myocarditis in our cohort. Additionally, we could not find any markers implying adverse outcomes in this relatively little number of patients, however this has to be confirmed by future studies including larger sample sizes.